2021
DOI: 10.3389/fnins.2021.646698
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration in Stroke Patients: A Theoretical Approach to Reinterpret Upper-Limb Proprioceptive Deficits and Visual Compensation

Abstract: For reaching and grasping, as well as for manipulating objects, optimal hand motor control arises from the integration of multiple sources of sensory information, such as proprioception and vision. For this reason, proprioceptive deficits often observed in stroke patients have a significant impact on the integrity of motor functions. The present targeted review attempts to reanalyze previous findings about proprioceptive upper-limb deficits in stroke patients, as well as their ability to compensate for these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…To try to formalize and quantify these predictions we applied an optimal theory of multi-sensory integration to the above-described task. This statistical model, in which the task is concurrently represented in the visual and proprioceptive space ( Tagliabue and McIntyre, 2008 , 2011 , 2012 , 2013 , 2014 ; McGuire and Sabes, 2009 ; Tagliabue et al, 2013 ; Arnoux et al, 2017 ; Bernard-Espina et al, 2021 ) allowed to compute the effects of changing posture in terms of subjects’ responses variability and in terms of the relative importance given to the visual and proprioceptive encoding of the information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To try to formalize and quantify these predictions we applied an optimal theory of multi-sensory integration to the above-described task. This statistical model, in which the task is concurrently represented in the visual and proprioceptive space ( Tagliabue and McIntyre, 2008 , 2011 , 2012 , 2013 , 2014 ; McGuire and Sabes, 2009 ; Tagliabue et al, 2013 ; Arnoux et al, 2017 ; Bernard-Espina et al, 2021 ) allowed to compute the effects of changing posture in terms of subjects’ responses variability and in terms of the relative importance given to the visual and proprioceptive encoding of the information.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare the Neck and Gravity Hypotheses predictions with the measured subjects’ precision and sensory weighting, we applied our “ Concurrent Model ” (see below) of multisensory integration ( Tagliabue and McIntyre, 2008 , 2011 , 2012 , 2013 , 2014 ; Tagliabue et al, 2013 ; Arnoux et al, 2017 ; Bernard-Espina et al, 2021 ) to the cross- and uni-modal tasks tested here.…”
Section: Introductionmentioning
confidence: 99%
“…However, adequately assessing deficits may be challenging. For example, touch and proprioception deficits are often missed due to a lack of consensus in clinical assessment methods, and can lead to errors in diagnosis ( 151 ) and inappropriate care. Vision and proprioception are predominant in the perception of spatial information, while hearing is useful in the perception of temporal information related to the periodicity, regularity, and speed of motion.…”
Section: Heterogeneity Of Sensory Deficitsmentioning
confidence: 99%
“…As a result, brain lesions affecting MSI processing can cause various problems such as feeling hyperactivated by sensory stimuli or having difficulty effectively integrating different sensory information (e.g., visual and auditory). For example, to move hands accurately, information from different sensory systems must be combined (e.g., visual, proprioceptive, and tactile systems) [ 18 ]. Originally, MSI was thought to be a process primarily controlled by bottom-up functions, but several studies have found that the multisensory integration process is also strongly linked to top-down processes, involving memory and attention [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%